Urinary tract infection and threatened preterm delivery in teenage pregnancies of a Peruvian Hospital - Abanto-Bojorquez, Dan (2020)
Introduction: The threatened preterm delivery can cause serious outcomes, so it is necessary toevaluate its causes. Objective: to determine if urinary tract infection (UTI) is a factor associated withthe threatened preterm delivery in pregnant teenages at the Hospital Sergio E. Bernales 2018 – 2019.Methods: Observational analytical case-control study. The study included pregnant teenages admittedto the gynecology and obstetrics service of the Hospital Sergio E. Bernales 2018 – 2019. Crude andadjusted ORs were calculated for possible confounding factors based on logistic regression models.Considering the p <0.05 value as significant. Results: The median age was 18 years. The results ofthe adjusted logistic regression model were that the threatened preterm delivery had a significantassociation with UTI (OR = 2.68, 95% CI: 1.3–5.3) and RPM (OR = 15, 95 CI. %: 5.9–37.9). Conclusion:Urinary tract infection is a factor associated with the threatened preterm delivery in pregnant teens.